Application of Homotopy Analaysis Method for linear integro-differential equations - Abbas, Zulkifly; Vahdati, Saeed; Ismail, Fudziah; Dizicheh, A. Karimi (Hikari, 2010)
This paper presents the application of the Homotopy Analysis Method (HAM) as a numerical solution to linear integro-differential equation. The HAM contains the auxiliary parameter h, that provides a powerful tool to analyze strongly linear and nonlinear problems. Examples are provided to demonstrate the advantages of HAM over the homotopy perturbation method (HPM), sine-cosine wavelets and CAS wavelets methods.